MoEpPOSS nanotaneciğinin PA6/TPE karışımlarının morfolojik ve reolojik özelliklerine etkisinin incelenmesi - Yıldırım, Rumeysa; Koçoğlu, Hürol; Ün, Merve; Ullah, Muhammad Saeed; Yakar, İpek; Ozkoc, Guralp; Kodal, Mehmet (İdris Karagöz, 2024)
Poliamit 6 (PA6) kimyasallara, yorulmaya ve aşınmaya karşı yüksek direnç ve yüksek tokluk gibi sahip avantajlara sahip bir mühendislik termoplastiğidir. Fakat çentik hassasiyeti ve düşük darbe direnci gibi dezavantajlara sahiptir. Bu tür istenmeyen özelliklerini bertaraf etmek için elastomerlerle karışımları hazırlanmaktadır. Son zamanlarda, yüksek elastikiyet, geri dönüştürülebilirlik ve kolay işlenebilirlik gibi üstün özelliklerinden dolayı termoplastik elastomer (TPE)'ler, PA6 gibi çentik hassasiyeti olan polimerlerin toklaştırılmasında sıklıkla kullanılmaktadır. Bilindiği üzere, polimer karışımlarında istenilen özelliklerin elde edilebilmesi karışımı oluşturan bileşenler arasındaki arayüzey etkileşimine bağlıdır. Uyumlaştırıcılar kullanılarak bu arayüzey etkileşimi elde edilebilmektedir. Son zamanlarda, polihedral oligomerik silseskuiokzan (POSS) organik/inorganik hibrit nanotanecikleri konvansiyonel olanlara göre alternatif bir uyumlaştırıcı olarak kullanılmaktadırlar. Bu çalışmada, PA6/TPE karşımlarının uyumlaştırılmasında tekli epoksi grubuna sahip POSS nanotanecikleri (MoEpPOSS) kullanılmıştır. MoEpPOSS ile uyumlaştırılmış PA6/TPE karışımlarının morfolojik ve reolojik özellikleri incelenmiştir.

Polyamide 6 (PA6) is one of the used engineering thermoplastics with the advantages of high resistance to chemicals and abrasion, high fatigue resistance and toughness. However, it has some disadvantages such as low impact strength and notch sensitivity. The blend of PA6 with elastomers can mitigate these shortcomings. Lately, thermoplastic elastomers (TPE) have been frequently used to toughen notch-sensitive polymers such as PA6 due to their outstanding properties such as high elasticity, recyclability, and easy processing. As it is known, obtaining superior properties in polymer blends relies on the interfacial interaction between the components of the blend. Additionally, by using compatibilizers, blends with the required properties can be created by enhancing interaction between phases, or interfacial adhesion. Recently, polyhedral oligomeric silsesquioxane (POSS) nanoparticles, organic/inorganic hybrid nanoparticles, are preferred as an alternative compatibilizer to conventional types. In this study, PA6/TPE blends were compatibilized with POSS nanoparticle with single epoxy group (MoEpPOSS). The morphological and rheological properties of PA6/TPE blends compatibilized with MoEpPOSS nanoparticle were investigated. Also, possible chemical interactions between PA6 and/or TPE and MoEpPOSS nanoparticle were determined via Fourier transform infrared spectroscopy (FTIR) analyses.
Investigation of effects of MoEpPOSS nanoparticle on the morphological and rheological properties of PA6/TPE blends
120M718
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri